1991
DOI: 10.1128/iai.59.1.346-350.1991
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Lewis rats with temperature-sensitive mutants of Mycoplasma pulmonis: adoptive transfer of immunity by spleen cells but not by sera

Abstract: Temperature-sensitive mutant vaccines protect rats against Mycoplasma pulmonis infection. The role of the humoral or cellular immune response in resistance to mycoplasma infection was investigated by adoptive-346

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, the role of cellular immune responses in mycoplasmosis appears to be controversial. The passive transfer of M. pulmonis-immune splenic lymphocytes protects against infection in rats (13). However, rats and mice that are deficient in T cells also develop less severe respiratory disease than do immunocompetent animals after infection with M. pulmonis (4).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the role of cellular immune responses in mycoplasmosis appears to be controversial. The passive transfer of M. pulmonis-immune splenic lymphocytes protects against infection in rats (13). However, rats and mice that are deficient in T cells also develop less severe respiratory disease than do immunocompetent animals after infection with M. pulmonis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the depletion of CD8 + T cells exacerbated pneumonia in a murine model of mycoplasma infection. [10][11][12] Compared to vaccines without adjuvant, inactivated vaccines with an adjuvant that was capable of inducing CD8 + T cell responses reduced lung lesion size in pigs with M. hyopneumoniae infection. [13] Live attenuated wholecell bacteria were used as attenuated mycoplasma vaccines, which induced activation of lung CD8 + T cells in vivo.…”
mentioning
confidence: 99%
“…Currently, animal colonies are monitored by the detection of specific antibody in serum that is elicited during infection with M. pulmonis, but it has been shown that animals can be infected and yet display seronegativity up to 4 weeks postinfection (5). In spite of these diagnostic antibody responses, data from Lai et al (25) have indicated that the principal protective feature of immunity to respiratory lesions caused by M. pulmonis may be cell-mediated immune responses. The same report also noted that while different strains of rodents have different susceptibilities to M. pulmonis, other studies suggest that preexisting antibody can be protective in mice but not in rats (25).…”
mentioning
confidence: 99%
“…In spite of these diagnostic antibody responses, data from Lai et al (25) have indicated that the principal protective feature of immunity to respiratory lesions caused by M. pulmonis may be cell-mediated immune responses. The same report also noted that while different strains of rodents have different susceptibilities to M. pulmonis, other studies suggest that preexisting antibody can be protective in mice but not in rats (25). Recognizing that the mucosal surfaces are the site of initial colonization and infection, it could be hypothesized that secretory immune responses are capable of interfering with the pathogenesis of this microorganism.…”
mentioning
confidence: 99%